Usefulness of computed tomography in the diagnosis of acute pyelonephritis in older patients suspected of infection with unknown focus. (February 2022) - Yano, Tetsuhiro; Takada, Toshihiko; Fujiishi, Ryuto; Fujii, Kotaro; Honjo, Hiroshi; Miyajima, Masayuki; Takeshima, Taro; Hayashi, Michio; Miyashita, Jun; Azuma, Teruhisa; Fukuhara, Shunichi
Background: In older adults, the diagnosis of acute pyelonephritis is challenging because of non-specific symptoms and false-positive urine test results. Few studies have investigated the diagnostic performance of computed tomography (CT) signs. Purpose: To evaluate the diagnostic performance of CT signs for acute pyelonephritis in older patients suspected of infection with unknown focus. Material and Methods: This cross-sectional study was conducted between 2015 and 2018. Patients aged ≥65 years who underwent blood cultures, urine culture, and non-contrast or contrast-enhanced CT on admission were included. Cases with clinically presumable infection focus before CT were excluded. Two radiologists blinded to clinical information independently reviewed five CT signs: perirenal fat stranding; pelvicalyceal wall thickening and enhancement; renal enlargement; thickening of Gerota's fascia; and area(s) of decreased attenuation. The final diagnoses were made by a clinical expert panel. Results: Among 473 eligible patients, 61 were diagnosed with acute pyelonephritis. When the laterality of findings between the left and right kidneys were considered, the positive and negative likelihood ratios of perirenal fat stranding were 4.0 (95% confidence interval [CI] = 2.3–7.0) and 0.8 (95% CI = 0.7–0.9) in non-contrast CT, respectively. The other signs in non-contrast CT showed similar diagnostic performance with positive and negative likelihood ratios of 3.5–11.3 and 0.8–0.9, respectively. Conclusion: CT signs can help physicians diagnose acute pyelonephritis in older patients suspected of infection with unknown focus.